THE PROPOSED BRICS CURRENCY IN LIGHT OF THE INTERNATIONAL ECONOMIC VARIABLES - Arshad Abdul Latif Turki; Abdul Rahman Karim Abdul Reda; Hussein breesam Habeeb (Scholar Express Journals, 2025)
The dominance of the dollar on international monetary transactions remains today, as it represents 90% of the volume of international trade exchanges, as a result of economic strength and global acceptance of its value and trust between dealers that gives it the ability to interfere in global economic and political decisions, The economies that follow the pattern of the opposition and deviate from the text to the domination of the G7, especially the third world countries and poor countries, often become victims of such interventions while trying to implement their own development policies that move beyond neutralizing comprehensive sanctions, this may give the impression of domination and control over several centuries and this included developed countries like Russia also under the trap of economic sanctions that called for efforts to reduce dominance The dollar, In this context to reduce the dominance of the dollar in international trade and ensure independent economic policies of countries, the BRICS bloc works in an alternative currency called Brices. One of the most prominent results reached by the research in light of geopolitical tensions and recent US sanctions on Russia, Iran, Iran is heading at a rapid pace to create a currency as protection against repeated sanctions by the United States by isolating it outside the system (Swift) ,One of the weighted scenarios is strongly the failure of the BRICS states to agree on a common currency due to economic and geopolitical challenges and for many reasons, foremost of which is the variation of priorities and goals for member states, each with different priorities and economic policies, and the most important thing is its weight in the international economic arena
Keywords: Proposed BRICS currency; BRICS; dollar dominance